Doenças inflamatórias intestinais na região Sudeste do Brasil: um estudo retrospectivo - Martins, Kamila Rosa (2017)
Introduction: Inflammatory bowel disease (IBD) has been increasingly diagnosed in South America. Although it has been extensively investigated in recent years, epidemiological data on the disease in Brazil are rare. Objective: To describe the clinical and epidemiological profile of patients with IBD treated at Hospital of Uberlândia clinics during the period from 1999 to 2014. Material and methods: A retrospective, descriptive and quantitative study was performed in the medical records of patients with IBD from confirmation Diagnosis, endoscopic examination and the variables age, sex, race, smoking habit, main diagnosis, as well as the location of diseases, main clinical manifestations, treatment instituted, complications related to IBD, extra-intestinal manifestations and drug treatment and / or Used. Results: 183 cases of IBD were evaluated, of which 91 patients were diagnosed with ulcerative colitis (RCU) and 92 with Crohn's disease (CD). The proportions of the incidence of IBD in females and males were 1.7 for RCU and 1.8 for DC. The mean age of patients with IBD was 35 years. The Caucasian ethnicity was predominant for both. The main symptoms were diarrhea, abdominal pain and intestinal colic. The most frequent complications were fistulas, enterorrhages and intestinal obstructions, and the main extraintestinal manifestations were the articular ones. The most commonly used therapy was medication, with aminosalicylates and immunomodulators being the most frequent. Conclusion: We found a profile very close to those found in the literature. The research allowed to conclude the low prevalence of IBD in the studied population when compared to North America, but high in relation to other regions considered with low incidence like Asia.